A comparison of cordocentesis outcomes between early and conventional procedures - Wirawit Piyamongkol (2018)
Objective: To compare procedural outcomes between early cordocentesis (1617 weeks) and those at 1822 weeks. Materials and Methods: A prospective database of cordocentesis was assessed. The eligible criteria included are (1) singleton pregnancy; (2) no fetal abnormalities; (3) gestational age of 1622 weeks and (4) procedures performed by experienced operators. The procedures performed during 1617 weeks were defined as early cordocentesis (Study group). The Control group (conventional cordocentesis; 1822 weeks) were selected by matching maternal age and years of procedures, with a ratio of 1:3. Results: Of 2942 eligible procedures, 103 procedures were undertaken during 1617 weeks and 309 matched controls were selected. Baseline characteristics of both groups were comparable. Time used to complete the procedure was significantly longer in Study group (8.45 ± 9.91 vs. 6.07 ± 6.63 min; p value 0.007). Similarly, rate of difficult procedures was significantly higher in Study group (7.8 vs. 2.3%; p value 0.011). However, rates of fetal loss, low birth weight infants and preterm births were not significantly different, but there was a tendency to be higher in Study group. Conclusion: Early cordocentesis is more difficult but relatively safe when performed by experienced hands, although it has a tendency to increase rates of adverse outcomes. This information may be helpful in counseling the couples. © 2012 Informa UK, Ltd.